The Status of the Study and the Possibility of Using Plant Species of the Genus Ferula L. In Uzbekistan - Yuldashov Murod Khudarganovich; Shomurotova Khurshida Bakhtiyorovna; Turobova Sadoqat Orif qizi; Sayimova Muxlisa Normurod qizi (International Journal on Orange Technologies, 2022)
This article is about the state of the study of plant species of the genus Ferula L. and about the chemical composition of this plant raw material, as well as the agro technology of its cultivation in Uzbekistan.